A Three-Phase Intervention Model for Systemic Governance Reform in National Sports Federations: The Case of Cyprus - Yiapanas, George (Standards-related Regional Innovation and International Cooperation, 2025)
This study addresses the critical governance challenges facing Cyprus's national sports federations, where persistent issues of financial opacity, leadership entrenchment, and resistance to reform hinder organizational effectiveness. Despite adopting the Code of Good Governance in 2018, implementation remains inconsistent due to resource constraints, ambiguous regulations, and cultural barriers. The research aims to develop a practical reform framework by adapting SIGA's Universal Standards to the Cypriot context, creating a mandatory yet supportive pathway for governance improvement. The study's significance lies in its dual contribution to theory and practice. Theoretically, it advances understanding of how to operationalize voluntary standards through enforceable, tiered systems. Practically, it provides Cyprus's sports authorities with actionable tools to overcome implementation barriers, while offering transferable lessons for international sports governance. Findings present a three-phase model (Bronze-Silver-Gold) that progressively builds governance capacity through: (1) mandatory transparency measures and basic compliance; (2) advanced accountability systems and leadership reforms; and (3) cultural institutionalization of governance values. Key innovations include digital compliance tools, subsidized governance officers, and incentive mechanisms linking certification to funding access. The framework successfully balances structural reforms with cultural change strategies, demonstrating how to transform governance from a compliance exercise to a strategic advantage. his research provides evidence that comprehensive reform requires both policy mandates and implementation support, offering a replicable blueprint for sports organizations seeking to enhance integrity while respecting contextual constraints. The adaptable tiered approach proves particularly effective for federations at different development stages, making governance improvement achievable across diverse organizational contexts.